Diagnosis and treatmnet of poisoning and drug overdose - Devarajan, TV (Jaypee Brothers Medical Publishers, 2015)
This book Diagnosis and Treatment of Poisoning and Drug Overdose was long-awaited by medical students, postgraduate, general practitioners, casualty medical officers and ICCU doctors. This book has been prepared keeping in mind the necessity for guiding junior doctors and doctors in CCU to give first-aid, investigate and give proper antidote for drug overdose.